Filmes de amido de amêndoa de manga: influência de nanocristais de amido e celulose - Silva, Ana Priscila Monteiro da (2017)
The objective of this work was to improve the tensile and barrier properties of starch films by incorporation of starch and/or cellulose nanocrystals, using seeds from Tommy Atkins mangoes as a source of these components. After extraction and characterization of starch, starch nanocrystals (SNC) and cellulose (CNC), starch films were prepared with SNC and/or CNC according to a central composite design, whose variables were the degree of substitution of SNC by CNC and the total percentage of nanostructures. Water vapor permeability (WVP) and tensile properties were defined as the responses. Starch with a good yield (38.8 %) and purity (~90%) was obtained, with granules varying in morphology (predominantly oval) and average size of 10.24 μm. Starch nanocrystals (SNC), with ovoid morphology, presented a mean dimension of 67.1 nm. The CNC resulted in a suspension with high Zeta potential (>50 mV). The optimization of the central composite design indicated as the best treatment the one with incorporation of 5% SNC and 5% CNC, which resulted in increases of about 90% and 70% in tensile strength and modulus respectively, besides a reduction of about 30% in WVP. In comparison with the film without nanostructures, this treatment did not show great differences in the crystallinity pattern or in thermal stability.